Anti-Mesothelin CAR-NK cells as a novel targeted therapy against cervical cancer - Kutle, Ivana; Polten, Robert; Stalp, Jan Lennart; Hachenberg, Jens; Todzey, Felix; Hass, Ralf; Zimmermann, Katharina; von der Ohe, Juliane; von Kaisenberg, Constantin; Neubert, Lavinia; Kamp, Jan C.; Schaudien, Dirk; et al. (Frontiers in Immunology, 2024)
Resistance to the currently available treatment paradigms is one of the main factors that contributes to poor outcomes in patients with advanced cervical cancer. Novel targeted therapy approaches might enhance the patient’s treatment outcome and are urgently needed for this malignancy. While chimeric-antigen receptor (CAR)-based adoptive immunotherapy displays a promising treatment strategy for liquid cancers, their use against cervical cancer is largely unexplored. This study used alpharetroviral SIN vectors to equip natural killer (NK) cells with a third-generation CAR (including CD28 and 4-1BB co-stimulatory domains) targeting Mesothelin, which was identified to be highly expressed on primary human cervical cancer tissues and cervical cancer cell lines in this and other studies. Anti-Mesothelin CAR-NK cells demonstrated high cytotoxicity against cervical cancer cells in 2D and 3D culture models, which corresponded to increased degranulation of CAR-NK-92 cells upon exposure to Mesothelin+ target cells. Mesothelin- cervical cancer cells were generated by CRISPR-Cas9-mediated knockout and used to show target antigen specificity of anti-Mesothelin CAR-NK-92 cells and primary NK cells derived from different healthy donors in co-culture experiments. Combination of anti-Mesothelin CAR-NK-92 cells with chemotherapy revealed increased elimination of cancer cells as compared to monotherapy settings. Our findings indicate the promise of anti-Mesothelin CAR-NK cells as a potential treatment option against cervical cancer, as well as other Mesothelin+ malignancies.